E-technologies for transformation of acquired knowledge into automated skills - Sergeyeva, Tetyana Viktorivna; Perelyhina, Olha Ihorivna; Novytska, Dariia Yevhenivna (CPN Publishing Group, 2021)
The article is devoted to the problem of acquired knowledge automation as a condition of the transformation of theory into practice in real life. The proposed approach, unlike with the traditional skill developing through frequent mechanical repetition of the pattern, is based on the innovative idea of conscious knowledge automation in the process of solving learning objectives that require solution estimate of efficiency. The phased developing strategy of the skill reposes in gradually curtailment the detailed analytical learning activities, carried out firstly in writing and then in oral form, with a gradual complication of the solution on account of a reduction in assistance in the form of instructions, mind maps, audio recordings of the model answers. There is a transition from a learning situation to a practical one with the transformation of analytical actions into a practical skill. Conscious mental actions are being automated, that allows returning to the conscious mode in case of an error or the need for new non-standard tasks solution. The prospect is to transfer innovative knowledge automation technology to other subject areas.
Keywords: transformation of theory into practice; knowledge automation; developing of skills; experience; abilities; mnemotechnics; e-learning technologies